2011
DOI: 10.5688/ajpe75229
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist Instruction of Physical Assessment for Pharmacy Students

Abstract: Objective. To assess the impact of a change from nurse to pharmacist instructors and a new curriculum intended to encourage students' use of physical assessment skills. Design. Pharmacist faculty members redesigned the physical assessment curriculum to focus on those assessment skills most likely to be performed by practicing pharmacists. The 5 focus areas were general assessment skills, gastrointestinal system, pulmonary system, central and peripheral nervous system, and cardiovascular system. Instructional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…The institutional setting may offer more opportunities for PA with better access to PA instruments, support from other health care providers, and peer encouragement. Furthermore, as schools of pharmacy begin to incorporate PA into their curriculum, new graduates of these programs may feel more comfortable utilizing these skills having some background through formal PA education [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The institutional setting may offer more opportunities for PA with better access to PA instruments, support from other health care providers, and peer encouragement. Furthermore, as schools of pharmacy begin to incorporate PA into their curriculum, new graduates of these programs may feel more comfortable utilizing these skills having some background through formal PA education [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Although pharmacy curriculums in North America have not traditionally included training in the area of PA, many Canadian and US schools of pharmacy have now incorporated PA into their curriculum [1][2][3][4]. The Canadian Pharmacist's Association (CPhA) Blue Print for Pharmacy: The Vision for Pharmacy acknowledges that future pharmacist education needs to emphasize foundational skills including PA [5].…”
Section: Introductionmentioning
confidence: 99%
“…To address this challenge, some colleges and schools pharmacy have enhanced their curriculum to teach physical examination as part of their physical assessment training. [3][4][5][6][7][8][9] Studies have found that pharmacist-led instruction and the use of simulation stethoscopes are effective in teaching physical examination skills to pharmacy students. 5,6 To date, no study has explored instructional strategies to implement an accelerated course in physical examination.…”
Section: Introductionmentioning
confidence: 99%
“…3 Currently, most pharmacy education literature describes efforts to redesign existing physical assessment instruction for pharmacy students but only one study describes how to implement a physical examination course within a PharmD program. [4][5][6][7][8][9] Longe described the implementation of a 3 credit-hour physical assessment course that met 5 hours per week. 8 To date, no study has described the implementation of an accelerated physical examination course with the use of multimedia and the flipped teaching method or evaluated the effectiveness of such a course for pharmacy students.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 However, few reports have described strategies for implementing a physical assessment program in pharmacy education. [10][11][12][13][14][15] More specifically, many of the previous studies used surveys to assess student satisfaction with the implementation of a new program rather than to assess the impact of the program on student learning. Others have described the way in which a physical assessment course is integrated within an existing course.…”
Section: Introductionmentioning
confidence: 99%